2015
DOI: 10.1530/jme-15-0217
|View full text |Cite
|
Sign up to set email alerts
|

Wisp1 mediates Bmp3-stimulated mesenchymal stem cell proliferation

Abstract: Adipose tissue expansion, resulting from adipocyte hyperplasia and/or hypertrophy, is a hallmark of obesity. Adipocytes are derived from mesenchymal stem cells (MSCs) through adipogenesis, a process involving three key steps: proliferation, commitment and differentiation. Although studies have elaborated on the mechanisms regulating adipocyte commitment and differentiation, the factors that control MSC proliferation remain largely unknown. Previously, we demonstrated that bone morphogenetic protein 3 (Bmp3), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…Circulating WISP1 concentration correlates with its expression in AT, which therefore represents a major source of this adipokine in humans [ 17 ]. Among the many cell types on which it exerts proliferative effects, WISP1 has induced proliferation of mesenchymal stem cells and, thus, AT expansion, in experimental models of visceral obesity [ 18 ].…”
mentioning
confidence: 99%
“…Circulating WISP1 concentration correlates with its expression in AT, which therefore represents a major source of this adipokine in humans [ 17 ]. Among the many cell types on which it exerts proliferative effects, WISP1 has induced proliferation of mesenchymal stem cells and, thus, AT expansion, in experimental models of visceral obesity [ 18 ].…”
mentioning
confidence: 99%
“…The WISP1 adipokine induces adipocyte progenitors and has been shown to be involved in adipocyte differentiation and migration (Al-Hamodi et al, 2014;Barchetta et al, 2017;Murahovschi et al, 2015). Cernea et al (2016) found that the WISP1 adipokine has a significant role in adipogenesis by the bone morphogenetic protein 3-dependent signaling pathway. Barchetta et al (2017) and Murahovschi et al (2015) reported that WISP1 expression was correlated to TG accumulation leading to adiposity.…”
Section: Wisp1 and Triglyceride Accumulationmentioning
confidence: 99%
“…WISP1 also is one of several components that control induced pluripotent stem cell reprogramming. WISP1 in conjunction with b-catenin is necessary for marrowderived mesenchymal stem cell differentiation and oversees bone morphogenetic protein-3 (BMP-3)-stimulated mesenchymal stem cell proliferation (Cernea et al 2016). WISP1 also can be differentially regulated during human embryonic stem cell and adipose-derived stem cell differentiation such that WISP1 expression is upregulated in human embryonic stem cells and repressed in adipose-derived stem cells during hepatic differentiation.…”
Section: Wisp1 In Cellular Repair and Proliferationmentioning
confidence: 99%